Parental Responses to Children's Chronic Pain: A Developmental Perspective on Parental Protectiveness, Minimization and Monitoring of Pain. - El-Behadli, Ana. (2017)
Abstract: Parental responses to children's pain are related to how children and adolescents cope with and manage chronic pain. However, research is needed to fully understand pediatric chronic pain from a developmental perspective. This study examined the effect of age on parents' responses to children's pain in a sample of 1,509 pediatric chronic pain patients. Pain characteristics were examined as possible moderators of the relations between child characteristics and parental responses to children's pain. Age was related to parental encouragement and monitoring with parents of older children being less encouraging and monitoring. Pain characteristics did not moderate relations between child's age and parental responses to children's pain. Findings regarding other child demographics, family demographics, child pain characteristics, and child functional disability and emotional distress are also reviewed. Implications for future research and chronic pain management interventions are discussed.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Child Study and Human Development.; Advisor: Ellen Pinderhughes.; Committee: Kerri Modry-Mandell, and Deirdre Logan.; Keywords: Clinical psychology, and Developmental psychology.